Diving deep – Qualifying as a science teacher - Dilruba Boksh, Thasmiah Khanom (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Meet Thasmiah Khanom, a dedicated science teacher making a real difference in secondary education. With a BSc in Biological Sciences from Queen Mary University and a PGCE from Greenwich University, Thasmiah has risen through the ranks to become the Head of Biology at a secondary school. Additionally, she plays a crucial role as an AQA examiner for GCSE and A-Level Biology. In an interview with second-year BSc Biomedical Science student Dilruba Boksh, Thasmiah shares her journey into teaching, the challenges she has overcome, and what keeps her motivated in the classroom. She also offers valuable advice for those considering a career in teaching, drawing on her journey and the insights she has gained along the way. The Editorial Team would like to thank Thasmiah for her time and contributions to this article.